2020
DOI: 10.1177/0093854820942274
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Crisis Intervention Teams in Prison to Improve Officer Knowledge, Stigmatizing Attitudes, and Perception of Response Options

Abstract: People with mental illness (MI) are overrepresented in prisons, in part, because people with MI stay in prison longer. Correctional officers (COs) use discretion in force, violations, and segregation. Crisis intervention teams (CITs) are being used in corrections to reduce disparities in sanctioning and improve safety. This quasi-experimental, mixed-methods study includes 235 CIT COs who were surveyed before and after training on knowledge of MI, stigmatizing attitudes, and perception of response options. Non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…To date, this is the first study to assess the use and impacts of CIT in a jail setting. And similar to the recent evaluation study of CIT training in prison (Canada et al, 2020), there were similar positive outcomes. Additionally, prior research on use and impact of CIT with law enforcement officers showed consistent improvements in officers’ knowledge and attitudes about mental health (Bonfine et al, 2014; Compton et al, 2008; Kubiak et al, 2017; Watson et al, 2017).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To date, this is the first study to assess the use and impacts of CIT in a jail setting. And similar to the recent evaluation study of CIT training in prison (Canada et al, 2020), there were similar positive outcomes. Additionally, prior research on use and impact of CIT with law enforcement officers showed consistent improvements in officers’ knowledge and attitudes about mental health (Bonfine et al, 2014; Compton et al, 2008; Kubiak et al, 2017; Watson et al, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…However, there is evidence suggesting that CIT-trained officers are more likely to transport individuals with SMI to crisis drop-off centers and community mental health services than their non-CIT trained counterparts (Kubiak et al, 2017;Taheri, 2016). Despite advocates for CIT expressing the need for specialized CIT trainings for correctional settings (Kerle, 2016), no studies were found that investigated the efficacy of training COs in jails (For a recent student on CIT training for COs in prisons: Canada et al, 2020). Therefore, this study asked: Does the CIT model have an impact in a county jail setting?…”
Section: Crisis Intervention Team Modelmentioning
confidence: 99%
“…First, this sample is from officers who self‐selected into taking the training and participating in research, and may not be representative of all officers across the state, or other states. Moreover, though previous research in the state has found that stigma was not associated with any socio‐demographic factors (Canada et al., 2020), since we did not collect these data, we cannot say with certainty that our findings were not influenced by these factors or that the sample is a representative sample. Second, though our model accounted for 79% of the variance in post‐test stigma, it is possible the regression models are missing key predictors of stigmatising attitudes that we did not collect in our data.…”
Section: Discussionmentioning
confidence: 70%
“…Further, these factors were not significantly associated with stigma in previous research with correctional officers (Canada et al, 2020). As a guide, most officers across the state are women (65%) and White (79%), with more than half of officers over the age of 50 (28%) or between 40 and 49 (32%).…”
Section: Data Collectionmentioning
confidence: 66%
See 1 more Smart Citation